Age-related increase in muscle stiffness is muscle length dependent and associated with muscle force in senior females - Jingfei Xu; Siu Ngor Fu; François Hug (BMC Musculoskeletal Disorders, 2021)
Abstract Background In aging, muscle stiffness is considered as one of the factors associated with the reduction of force generation capability. There have been inconsistent findings on age-related alteration in the passive stiffness of quadriceps muscle in the female adults. Thus, the aim of this study was to determine the effect of aging on the shear moduli of the superficial muscle heads of the quadriceps and to explore its relationship with knee extension force. Methods Passive shear moduli of the rectus femoris (RF), vastus lateralis (VL), and vastus medialis (VM) were measured at rest using shear wave elastography in 20 young and 20 senior female adults. Measurements were repeated at four knee joint positions, that is, 30°, 60°, 90°, and 105° of knee flexion. Maximal isometric voluntary knee extension force was assessed at 30°, 60°, and 90° of knee flexion. Results As per our findings, senior adults were determined to have significantly higher passive muscle shear moduli in the RF (by 34% – 68%; all p < 0.05) and the VL muscle heads (by 13%–16%, all p < 0.05) at and beyond 60° of knee flexion. Age-related increase in the VM was evident at 105° knee flexion (by11%, p = 0.020). The RF shear modulus was negatively correlated to the maximal isometric voluntary contraction force measured at 60° (r =  − 0.485, p = 0.030) in senior adults. Conclusions Senior female adults had greater passive stiffness at the superficial muscle heads of the quadriceps muscles when measured at long muscle length. Among the senior female adults, the passive stiffness of RF has been determined to have a negative association with the knee extensor force only at 60° knee flexion. No significant association was noted for other angles and muscles.